MIRZO ULUGBEK’S CONTRIBUTION TO UZBEK AND WORLD SCIENCE (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Mirzo Ulugbek was one of the unique people in the Timurid dynasty, who made an invaluable contribution to the development of science and culture. Mirzo Ulugbek was the son of Shahrukh and the grandson of the great Tamerlane (9 April 1336 – 17–18 February 1405) who was a Turco-Mongol conqueror founded the Timurid Empire in and around modern-day Afghanistan, Iran, and Central Asia, becoming the first ruler of the Timurid dynasty. [1;23] The main goals and objectives of the article are formulated. Based on the observation, Ulugbek is not only an astronomer, but also a mathematician, enlightener, poet and historian. The study shows the scientific and cultural heritage in the Timurids era and to create the invaluable work “Star tables of Ulugbek” that causes admiration and surprise of the whole world.